1986
DOI: 10.1002/dev.420190202
|View full text |Cite
|
Sign up to set email alerts
|

Development of auditory localization in dogs: Single source and precedence effect sounds

Abstract: The development of auditory localization in dogs was investigated in a litter of 12 pups. Behavioral auditory localization consisted of orienting responses to dog vocalizations presented from loudspeakers 90 degrees to each side. Sounds were presented in two configurations, single source (only one loudspeaker) and precedence effect (both loudspeakers, with one slightly leading the other). Localization began around 16 days after birth, for single-source sounds. This is consistent with previous observations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Furthermore, the average time at which hand‐reared German shepherds reliably responded to sound was less than a week different from mother‐reared German Shepherds and wolves (Hand‐reared German shepherds: 4.3 wk; Mother‐reared German shepherds: 3.7 wk; Wolves: 3.7 wk) and matches well with previous literature (Fox , ; Ashmead et al. ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore, the average time at which hand‐reared German shepherds reliably responded to sound was less than a week different from mother‐reared German Shepherds and wolves (Hand‐reared German shepherds: 4.3 wk; Mother‐reared German shepherds: 3.7 wk; Wolves: 3.7 wk) and matches well with previous literature (Fox , ; Ashmead et al. ).…”
Section: Discussionsupporting
confidence: 89%
“…Observational data were deemed unnecessary for dogs because the timing of the onset of visual and auditory systems is well established and previous experiments are comparable to these methods (Fox , , ; Scott & Fuller ; Fox & Weisman ; Ashmead et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar sequence of development has been found in another species, dogs. Ashmead, Clifton, and Reese (1986) found that puppies first began to orient toward a single-source, nonechoing sound at 16 days of age, but failed to orient toward precedence effect sounds. Although the cortical-mediation hypothesis remains an intriguing possibility, its final evaluation requires further research on the development of orientation responses in animals and their relation to neurophysiological development at higher levels of the nervous system.…”
Section: Discussionmentioning
confidence: 98%